Storage of whole-tree chips from high-density energy plantations of Eucalyptus in Brazil. (October 2016) - Eufrade Junior, Humberto de Jesus; Oguri, Guilherme; de Melo, Raoni Xavier; Ballarin, Adriano Wagner; Guerra, Saulo Philipe Sebastião
Abstract: In this paper, the drying of whole-tree chip (WTC) storage from young Eucalyptus plantation managed at short-rotation coppice in Brazil was studies. The biomass was converted from high-density energy plantations of Eucalyptus grandis at 2 years old into four piles. Wood chip particles had 5, 15, and 30 mm length were disposed on a paved surface to evaluate the effect on the chip drying. An additional covered pile (30-mm wood chip) was installed to evaluate the effect of coverage condition. The non-ventilated and uncovered piles were not affected by WTC length, and the final moisture content (MC) was 48.4–53.5% and temperature inside the piles (storage temperature) was approximately 36 °C. However, the coverage showed beneficial effect on drying wood chip process, collaborating to keep the MC lower than 35%, conventionally recommended for energy purposes. Among storage systems studied, the higher daily moisture content was assigned to covered pile, about 0.197% day −1 during the first 30 days. This paper can be used as a reference for further studies with wood chip pile storage at tropical conditions. Highlights: The chip length and coverage condition were tested on SRF eucalypt whole-tree chip stored in small piles. The storage period lasted 126 days, winter and spring (initial period) at tropical condition. Moisture content of non-ventilated and uncovered piles were not effect by whole-tree chips length. Coverage treatment had beneficial effect on whole-tree chip drying.